Thermostatted dual-channel portable capillary electrophoresis instrument - Koenka, Israel Joel; Küng, Nina; Kubáň, Pavel; Chwalek, Thomas; Furrer, Gerhard; Wehrli, Bernhard; Müller, Beat; Hauser, Peter C (Electrophoresis, 2016)
A new portable CE instrument is presented. The instrument features the concurrent separation of anions and cations in parallel channels. Each channel has a separate buffer container to allow independent optimization of separation conditions. The microfluidics circuit is based on off-the-shelf parts, and can be easily replicated; only four valves are present in the design. The system employs a miniature automated syringe pump, which can apply both positive and negative pressures (-100 to 800 kPa). The application of negative pressure allows a semi-automatic mode of operation for introducing volume-limited samples. The separations are performed in a thermostatted compartment for improved reproducibility in field conditions. The instrument has a compact design, with all components, save for batteries and power supplies, arranged in a briefcase with dimensions of 52 × 34 × 18 cm and a weight of less than 15 kg. The system runs automatically and is controlled by a purpose-made graphical user interface on a connected computer. For demonstration, the system was successfully employed for the concurrent separation and analysis of inorganic cations and anions in sediment porewater samples from Lake Baldegg in Switzerland and of metal ions in a sample from the tailing pond of an abandoned mine in Argentina.
Keywords: CE; Reproducibility of Results; Microfluidics; kalibrace; reprodukovatelnost výsledků; Calibration; Automation; uživatelské rozhraní počítače; Electrophoresis, Capillary; User-Computer Interface; Environmental monitoring; On-site measurements; Portable devices; automatizace; elektroforéza kapilární; mikrofluidika